Taenia solium infection in Peru: a collaboration between Peace Corps Volunteers and researchers in a community based study. - Nathaniel S Watts; Monica Pajuelo; Taryn Clark; Maria-Cristina I Loader; Manuela R Verastegui; Charles Sterling; Jon S Friedland; Hector H Garcia; Robert H Gilman; Cysticercosis Working Group in Peru (PLoS ONE, 2014)
Neurocysticercosis is a leading cause of seizures and epilepsy in most of the world, and it occurs when Taenia solium larval cysts infect the central nervous system. T. solium tapeworm infection is endemic in much of Peru, but there are scarce data on the prevalence in many rural highland communities where it is likely to be hyper-endemic. Peace Corps Volunteers live and work in these communities; however, to our knowledge, they have not been used to facilitate public health research.We utilized Peace Corps Volunteers to estimate the prevalence of T. solium tapeworm infection in seven rural communities in northern Peru. A convenience non-random sampling frame was used. Peace Corps Volunteers facilitated the collection of stool samples (N = 2,328), which were analyzed by sedimentation and microscopy. Niclosamide treatment and purgation preceded species identification, which was done by PCR-REA.Taenia sp. egg-positive stool samples were found in three of the seven communities we surveyed. The overall prevalence of Taenia sp. egg positivity was 2.1% (49/2,328) (95% CI = 1.6-2.8%) with prevalence up to 4.3% (42/977) (95% CI = 3.1-5.8%) by community. All 34 of the specimens tested by PCR-REA were T. solium. The overall prevalence of T. solium tapeworm infection was 1.5% (34/2,328) (95% CI = 1.0-2.0%). Prevalence up to 2.9% (28/977) (95% CI = 1.9-4.1%) by community was observed.This study recorded high T. solium tapeworm prevalence, and identified hyper-endemic rural communities. It demonstrates that synergy between researchers and Peace Corps Volunteers can be an effective means to conducting large-scale, community-based studies in remote areas of Peru.